Nanomaterials - Toxicity and Risk Assessment 2015
DOI: 10.5772/60796
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Self-assembly of Functionalized Nanocomposites and Nanomaterials – Relationship Between Structures and Properties

Abstract: The recent progress in nanocomposites and nanomaterials is varied and occupies various fields. Nanocomposites can be prepared with a variety of special physical, thermal, and other unique properties. On the other hand, self-assembly technique is playing an important role in preparing well-defined multilevel nanostructures and the functionalized surface with the designed and controlled properties. In this chapter, various kinds of nanocomposites including gold nanoparticles, inorganic-organic hybrid composites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…It can be observed that the lamellar structure of GO-1 (Figure 3b-d) presents thinner layers than the initial graphene oxide, as well as the expected smooth surfaces with wrinkles and folded regions. These observations could be accounted for by the sp 3 carbons, the formation of oxygen-containing functional groups in the basal planes, and to various GO structural defects [40]. The reduction of oxygen-containing functional groups located in the basal plane of the sp 2 carbon hybridization allowed the lamellas of the GO to be held together via weak van der Waals forces [22].…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the lamellar structure of GO-1 (Figure 3b-d) presents thinner layers than the initial graphene oxide, as well as the expected smooth surfaces with wrinkles and folded regions. These observations could be accounted for by the sp 3 carbons, the formation of oxygen-containing functional groups in the basal planes, and to various GO structural defects [40]. The reduction of oxygen-containing functional groups located in the basal plane of the sp 2 carbon hybridization allowed the lamellas of the GO to be held together via weak van der Waals forces [22].…”
Section: Resultsmentioning
confidence: 99%
“…Nanocomposites and nanomaterials have been attracting increasing attention in various fields [1][2][3][4][5][6]. Nanocomposites can be prepared with a variety of special physical, thermal, and other unique properties.…”
Section: Introductionmentioning
confidence: 99%